The Effect of Nursing Supervision on the Quality of Interprofessional Collaboration Among Nurses in Inpatient Wards - Anih Anih; Muhammad Hadi; Naryati Naryati; Harif Fadhillah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Interprofessional Collaboration (IPC) is essential for improving healthcare quality and patient safety in inpatient settings. This study aimed to analyze the effect of nursing supervision on IPC quality in inpatient wards. A quasi-experimental design was used with intervention and control groups, each consisting of 20 nurses with total sampling. IPC quality was measured five times (p1–p5) using an IPC instrument. The intervention group received structured nursing supervision, while the control group did not receive any intervention. The data were analyzed using descriptive and inferential statistics with multivariate analysis with GLM. The results showed a significant and consistent increase in IPC scores in the intervention group from the first to the fifth measurement, whereas the control group showed only a slight improvement. Multivariate analysis yielded a p-value of 0.001, indicating a statistically significant difference between the two groups. In conclusion, nursing supervision significantly improves the quality of Interprofessional Collaboration in inpatient wards.